Early–middle Jurassic source to sink evolution and its tectonic significance in the northeastern Sichuan Basin - Hong, HaiTao; Qin, ChunYu; Zhang, ShaoMin; Zhang, ZhiJie; Wang, XiaoJuan; Li, Nan; Cheng, DaWei; Tang, Wenbin (Frontiers in Earth Science, 2023)
This paper discusses the sedimentary environment and source supply in the sedimentary area and their coupling relationship through a detailed description of the deposits from the Ziliujing Formation to Shaximiao Formation of the Lower-Middle Jurassic on the Tieshan section in the Dazhou City, northeastern Sichuan Province, through sedimentary characterization, determination of paleocurrent direction, analysis of heavy minerals, and detrital zircon U-Pb dating. The results show that the Zhenzhuchong Member is sufficiently supplied with detrital sediments and is dominantly composed of fluvial-delta deposits. The Dongyuemiao Member-the first 2 member of Lianggaoshan Formation is dominated by lacustrine deposits, with the detrital supply increased initially in the early Lianggaoshan. The second member of Lianggaoshan Formation suggests a significant increase of detrital supply, with the lake basin shrunk and the paleocurrent direction changed. The Shaximiao Formation reveals a complete disappearance of lake basin in the northern Sichuan Basin. The comprehensive analysis on source supply indicates that the change of source property is apparently coupled with the change of sedimentary environment, both controlled by orogenesis around the basin. It is inferred from the zircon age distribution that the changes of sedimentary environment and source supply during the late Ziliujing period and the middle and late Lianggaoshan period are resulted from the uplifting of Micangshan Mountain, Dabashan Mountain and Qinling Mountain respectively.